ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KESUKSESAN IMPLEMENTASI SISTEM E-FILING PAJAK - Muh. Ihsan A.R.; Azwar Azwar (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2018)
In order to address the task and function in tax policy through the information technology, the Directorate General of Tax, Ministry of Finance of Indonesia, has already developed and launched e-Filing system as tax services in web based. Although it has massively run, there are still problems in its implementation. Hence, we need to evaluate and judge how its implementation based on point of view of its user. The general purpose of this research is to evaluate the success of e-Filing system implementation based on user perception with DeLone & McLean Information System Success Model Approach (1992). By using primary data form questionnaire and secondary data with quantitative approach of Structural Equation Modelling (SEM) based on Partial Least Square (PLS)’s component or variance, this research examine the effect of success indicators measurement on implementation of e-Filing system based on Delone & McLean (1992) model. This model uses six variables which are system quality, information quality, user satisfaction, use, individual impact and organizational impact. This research empirically showed that the e-Filing system currently implementated is not successfully running yet based on all DeLone & McLean’s success measurement criterias. Hence, Directorate General of Tax need to improve, strengthen, and expand the e-Filing system implementation.